Life history and nesting traits reflect urban tolerance in coastal birds - Sarah L. Jennings; Emma M. Garrison; Clinton D. Francis (Royal Society Open Science, 2025)
Rapid urbanization has prompted considerable interest in understanding which species thrive or fail in these novel environments. Because half of the human population resides in coastal areas, studies that explicitly examine urban tolerances among coastal species are needed. Here, we sought to explain variation in coastal bird tolerances to urban habitats with species life history, diet, nest, social, sensory and sexual selection traits using phylogenetically informed models and three urban-tolerance indexes. We found that nest site height was the strongest predictor, with species nesting in elevated locations exhibiting greater urban tolerance, probably due to reduced anthropogenic disturbances and risk of predation. Life-history traits, including larger clutch sizes and lower brood value, reflecting more lifetime breeding attempts, also predicted urban tolerance, suggesting that fast reproductive strategies buffer against urban-associated risks. Contrary to our prediction, species with altricial young displayed higher urban tolerance, potentially due to shorter incubation and fledging times. Collectively, our results suggest that many of the predictors related to urban tolerance in songbirds also predict tolerances among a broader swath of avian diversity. Such knowledge should help researchers forecast the composition of coastal, urban bird communities in the future and will inform efforts to conserve functionally diverse coastal ecosystems.